Relationship-Specificity, Contract Enforceability, and Income Smoothing - Dou, Yiwei; Hope, Ole-Kristian; Thomas, Wayne B. (The Accounting Review, 2013)
ABSTRACT: Contracting parties, such as the firm and its supplier, have cost-reducing incentives to make investments that support the unique transactions between them. However, to the extent that one party may renege on its contractual obligations, the other party incurring the cost of the relationship-specific investment bears additional risk and is less willing to invest such that sub-optimal investment occurs. In countries where enforceability of explicit contracts is particularly weak, parties have incentives to signal their willingness to fulfill implicit claims and maintain long-term relationships. We predict that firms engage in income smoothing to send such a signal to their suppliers. Consistent with these expectations, we find that firms that both reside in countries with weak contract enforceability and operate in industries with a greater need for relationship-specific investments tend to smooth reported income more. We further decompose income smoothing into “informational” and “garbled” components and find that results are driven by the informational component of income smoothing. Our results support the important role that accruals play in providing information in the presence of incomplete contracts. JEL Classifications: F14, K12, L14, M41, M43